The Challenges of Intergovernmental Organizations in Combating Transnational Crime: An Indonesian Perspective - Muhammad, Rifki; Roziqin, Ali; Susilo, Denny; Romadhan, Ach. Apriyanto (Cakrawala, 2024)
Human trafficking is a pressing global issue, especially in the Southeast Asian region, where Indonesia plays a role as a country of origin, transit and destination. This study aims to identify the cooperation between the Indonesian Police and ASEANAPOL using descriptive qualitative research methods. This research also highlights the role of ASEANAPOL through 4 strategies of handling Indonesian Police in collaboration with ASEANAPOL which include capacity building through training (ATCM), international meetings (AMMTC and SOMTC), electronic-based real-time information exchange (System e-ADS), and strengthening cross-border investigation mechanisms through the Joint Coordination System (JCS) with border guarding and dispatching personnel such as Attache POLRI (ATPOL) and POLRI Technical Staff (STAFNISPOL). While this research focuses on preventive responses to human trafficking, there are limitations that need to be considered, including aspects of prevention and prosecution involving victim identification and protection. Future research is recommended to explore all aspects, including prevention and prosecution measures, to develop ASEANAPOL’s organisational framework in addressing transnational crimes.